Stakeholderorientierung, Systemhaftigkeit und Stabilität der Corporate Governance in Deutschland - Reinhard H. Schmidt (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2006)
In diesem Beitrag möchte ich die drei Merkmale Stakeholderorientierung, Systemhaftigkeit und Stabilität der Corporate Governance speziell für den deutschen Fall beschreiben und analysieren und den skizzierten Zusammenhang zwischen ihnen näher untersuchen. Ich beginne im nächsten Abschnitt mit einer knappen allgemeinen Kennzeichnung der Corporate Governance in Deutschland und in den angelsächsischen Ländern. Der dritte Abschnitt ist der Frage gewidmet, ob auch die Interessengruppen, die nicht zugleich Aktionäre sind und die man inzwischen auch im Deutschen als "Stakeholder" bezeichnet, in der Corporate Governance, aus ökonomischen Gründen eine aktive Rolle spielen sollen. Ich werde diese Frage positiv beantworten: Ja, im Prinzip ist dies sinnvoll. Dies trifft besonders für Deutschland zu und gilt speziell für zwei Gruppen von Stakeholdern: die Banken als Kreditgeber und die Mitarbeiter. Und es gibt durchaus Gründe zu vermuten, dass die Argumente, die für eine Stakeholderorientierung sprechen, in der Zeit der beschleunigten Globalisierung gewichtiger sind, als sie je waren. – – Since the time of Germany's belated industrialisation, corporate governance in Germany has been stakeholder oriented in the dual sense of attaching importance to the interests of stakeholders who are not at the same time shareholders, and of providing certain opportunities for these stakeholders to influence corporate decisions. Corporate governance is also systemic. It is a system of elements that are complementary to each other, and also consistent. In other word, it is composed of elements for which it is important that they fit together well, and in the German case these elements did fit together well until quite recently. Corporate governance as a system is itself an element of the German bank-based financial system at large and possibly even of the entire German business and economic system. Stakeholder orientation of governance is consistent with the general structure this system, and even represents one of its central elements. In retrospect, German corporate governance has also proved to be surprisingly stable. Its fundamental traits date back to the turn from the 19th to the 20th century. There are strong reasons to assume that the systemic features, that is, its complementarity and consistency, have greatly contributed to its past stability. Since about ten years now, there are growing tendencies to question the viability and stability of the German corporate governance system and even the financial system as a whole. One of the central topics in the new debate concerns the stakeholder orientation of the system, which some observers and critics consider as the main weakness of the ?German model? under the increasing pressures of globalisation and European integration. As far as their development over time is concerned, systems of complementarity elements exhibit certain peculiarities: (1) They do not adjust easily to changing circumstances. (2) Changes concerning important individual elements, such as the stakeholder orientation of governance, tend to jeopardize the viability and the stability of the entire system. (3) While they appear to be stable, systems shaped by complementary may simply be rigid and tend to break under strong external pressure. ?Breaking? means that a system undergoes a fundamental transformation. It seems plausible to assume that the German financial system is already in the middle of such a transformation. It is yet another consequence of its systemic character that this transformation is not likely to be a smooth and gradual process and that it will not lead to a ?mixed model? but rather to the adoption of a capital market-based financial system as it prevails in the Anglo-Saxon countries. In such a system, corporate governance cannot be geared to catering to the interests of stakeholders, and an active role for them would not even make any economic sense.
Keywords: 330